Bacterial lipids: powerful modifiers of the innate immune response [version 1; referees: 2 approved] - Courtney E. Chandler (F1000Research, 2017)
The innate immune system serves as a first line of defense against microbial pathogens. The host innate immune response can be triggered by recognition of conserved non-self-microbial signature molecules by specific host receptor proteins called Toll-like receptors. For bacteria, many of these molecular triggers reside on or are embedded in the bacterial membrane, the interface exposed to the host environment. Lipids are the most abundant component of membranes, and bacteria possess a unique set of lipids that can initiate or modify the host innate immune response. Bacterial lipoproteins, peptidoglycan, and outer membrane molecules lipoteichoic acid and lipopolysaccharide are key modulators of the host immune system. This review article will highlight some of the research emerging at the crossroads of bacterial membranes and innate immunity.